Ultrastructural changes on the hard palatine mucosa of Calomys callosus after 120 days of experimental chronic alcoholism - Martinez, M.; Milton, F. A.; De Oliveira, S. A.; De Lima, N. F.; Segatelli, T. M.; Pinheiro, P. F.F.; Almeida, C. C.D.; Mello, W.; Quitete, V. H.A.C.; Martinez, F. E. (My University, 2005)
The present study analyzed the toxic effects of chronic alcohol ingestion on the ultrastructure of the lining epithelium of the hard palatine mucosa of the rodent Calomys callosus, in order to contribute to the understanding of the consequences of alcohol abuse for the morphology of the digestive system. Twenty-six adult animals aged three months were divided into two experimental groups. The control group received a solid diet and tap water, and the alcoholic group received the same solid diet and ethanol P.A. diluted 20% in water (v/v). After 120 days of treatment, all animals were anaesthetised, weighed and sacrificed. At the end of treatment, mean body weight did not differ between control and alcoholic animals. The epithelial cells of the alcoholic group showed many alterations such as the presence of lipid droplets, nuclei in corneum layer, nuclei with increase peripheral chromatin and greater electron density, altered mitochondria, and intense dilatation of the intercellular spaces. It was concluded that 20% ethanol provokes marked ultrastructural lesions in the hard palatine mucosa.
Keywords: Alcoholism; Calomys callosus; Epithelium; Hard palate; Lamina propria; Mucosa